USE OF SAND AS A COMPONENT OF MULTI SOIL LAYERING (MSL) SYSTEM TO MINIMIZE LIQUID WASTE CONTAMINANT OF CRUDE PALM OIL (CPO) - Citra Pratiwi Sidebang; Syafnil Syafnil (Jurnal Agroindustri, 2017)
Purpose of this research was to determine a capability of MSL-sand in reducing contaminants out of the liquid waste of CPO; to determine optimal rate of flow and; to determine the efficiency of MSL-sand in reducing oil-fat, BOD, COD and pH of liquid waste of CPO.  The research was done by flowing liquid waste through an MSL-sand with a rate of flow were0.3 L/hour, 0.6 L/hour, 0.9 L/hour, and 1.2 L/hour; each of treatment was repeated three times. Result of the research showed that with rate of flow of 0.3 L/hour, 0.6 L/hour, 0.9 L/hour, and 1.2 L/hour, the MSL-sand was capable of reducing oil-fat from 471.6 mg/L to 21.30 mg/L, 33.40 mg/L, 43.47 mg/L, and 55.30 mg/L respectively;BOD from 412 mg/Lto 6.73 mg/L,19.27 mg/L,33.10 mg/L, and46.93 mg/L respectively;COD from 1237 mg/L to  31.33 mg/L, 61.67 mg/L, 98.33 mg/L, and135.00 mg/L respectively;and pH from 9.00to 6.72,6.88,7.21 and7.36 respectively.  The optimal rate of flow to reduce liquid waste contaminant was 0.3 L/jam (class III) and 0.4 L/jam (class IV). Efficiency of the MSL-sand with the rate of flow of 0.3 L/jam,0.6 L/jam,0.9 L/jam, dan 1.2 L/jam in reducing oil-fat was 95.48 %, 92.92 %, 90.78 %, and88.27 % out of 471.6 mg/L; COD was  97.47 %, 95.01 %,92.05 %, and89.06 % out of 1237 mg/L; and BOD was98.37 %, 95.32 %, 91.97 %, and88.61 %out of 412 mg/L. Reduce of contaminant out of the liquid waste of CPO proved that MSL-sand was capable of reducing oil-fat, COD and BOD and also neutralize the pH.